2020
DOI: 10.1111/pin.12971
|View full text |Cite
|
Sign up to set email alerts
|

Elastin and collagen IV double staining: A refined method to detect blood vessel invasion in breast cancer

Abstract: Blood vessel invasion (BVI) is a prognostic indicator in various cancers. Elastic stain, which highlights blood vessel walls, is commonly used to detect BVI. In the breast, however, its diagnostic usefulness is limited because it also highlights some intraductal carcinoma components, which often mimic BVI. In this study, we aimed to improve BVI detection in breast cancer and developed a double staining: Victoria blue for elastin and immunohistochemistry for collagen IV. Collagen IV fibers were retained along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Approximately 40% of patients with ER-positive breast cancer have defects in the DNA repair mechanism, which is an important factor contributing to endocrine resistance in breast cancer. A study revealed that compared to patients with low ERCC1 expression, (30,31). Multivariate regression analysis revealed that vascular tumor thrombus is an independent prognostic factor for patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40% of patients with ER-positive breast cancer have defects in the DNA repair mechanism, which is an important factor contributing to endocrine resistance in breast cancer. A study revealed that compared to patients with low ERCC1 expression, (30,31). Multivariate regression analysis revealed that vascular tumor thrombus is an independent prognostic factor for patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This increases the risk of lymph node and distant metastasis in patients with breast cancer. Vascular tumor thrombus indicates poor prognosis in patients with breast cancer and can predict distant metastasis and local recurrence of tumors ( 30 , 31 ). Multivariate regression analysis revealed that vascular tumor thrombus is an independent prognostic factor for patients with breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…H&E, D2-40, CD31, CD31 and collagen IV double staining were performed by the conventional immunohistochemistry method. Elastin and collagen IV double staining was performed as described previously [23]. Complete information on the antibodies and the staining procedures can be found in Supplementary Tables S1-S3.…”
Section: Tissue Staining By Immunohistochemistrymentioning
confidence: 99%
“…Histological analysis MVD, GMP, C-shaped, and excessively branched capillaries were investigated for each case. Lymphatic vessel invasion and blood vessel invasion were analyzed as described previously [23]. In the invasive tumor areas, the structure of the blood vessel can be identi ed by a brown-stained structure with or without lumen using CD31 single staining.…”
Section: Tissue Staining By Immunohistochemistrymentioning
confidence: 99%
“…Detecting blood vessel invasion in breast cancer is of limited diagnostic usefulness due to the components of intraductal carcinomas mimicking blood vessel invasion. A study by Fujisawa et al used a combination stain of Victoria blue for elastin and IHC for collagen type IV [64]. This allowed the differentiation between the tissues of vascular origin, which would show reigned or lost collagen fibers, and the tissues of intraductal carcinoma, which would show a normal arrangement of the collagen in the basement membrane [64].…”
Section: Use Of Elastin Stains In Malignancies Other Than Colorectal ...mentioning
confidence: 99%